Assessment of left heart dysfunction to predict doxorubicin cardiotoxicity in children with lymphoma - Chen, Jiaqi; Cheng, Chunyue; Fan, Li; Xu, Xiaochuan; Chen, Jing; Feng, Yang; Tang, Yi; Yang, Chunjiang (Frontiers in Pediatrics, 2023)
Objectives: To assess the changes in the left myocardial after chemotherapy for childhood lymphoma and observe the predictive value for cancer treatment-related cardiac dysfunction (CTRCD) by Speckle-tracking echocardiography (STE). Methods: A total of 23 children with histopathological diagnoses of lymphoma were included, with age-matched normal controls. Comparative analysis of clinical serological tests and left heart strain parameters in children with lymphoma, including Left ventricular global longitudinal strain (LVGLS); global myocardial work (GMW) indices, which include global work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE); the LS of sub-endocardial, middle and sub-epicardial layers myocardium during left ventricular systole were measured; left atrial strain of reservoir phase (LASr), left atrial strain of conduit phase (LAScd), left atrial strain of contraction phase (LASct). Results: Binary logistic regression analysis showed that GLS was the most sensitive predictor for detecting patients at lofty risk of anthracycline-related cardiotoxicity. Both before and after chemotherapy, GLS in the left ventricle showed a pattern of basal segment < middle segment < apical segment and sub-epicardial < middle < sub-endocardial layer (p < 0.05), and the degree of decreased also showed revealed a regular pattern of epicardial layer < middle layer < subendocardial layer while the difference was not significant (p > 0.05). After chemotherapy, E/A and LAVI of each group were in the normal range, and the overall mean values of LASr, LAScd and LASct slightly increased in the second cycle and decreased significantly in the fourth cycle after chemotherapy, reaching to the lowest level, LASr and LAScd were positively correlated with GLS. Conclusion: LV GLS is a sensitive indicator to predict CTRCD compared with conventional echocardiography-related parameters and serological markers, GLS of each myocardial layer showed a certain regularity. Left atrial strain can be used for early monitoring of cardiotoxicity in children with lymphoma after chemotherapy.